80 mm-wide cold atmospheric-pressure plasma generated by two parallel but horizontally separated electrodes. (16th March 2015) - Chen, Qiang; Ichiki, Takanori
Abstract: 80 mm-wide helium cold atmospheric-pressure plasma (CAPP) was generated via two parallel but horizontally separated electrodes. The CAPP is considered to be essentially a positive streamer, and the separated electrodes suppress arc transition of the CAPP. Both the electrodes' distance and He flow rate at medium values favor plasma expulsion. The optical emission spectra of the CAPP demonstrate that He related species are dominant inside the plasma generator, while the main species downstream are radicals of OH, atomic O, γ -NO and N2 related species. In addition, the gas temperature of the CAPP simulated OH line (309 nm) is approximately room temperature.